Priest Luka Popović parishioner of Suvi Do (March 1st 1890 - February 21st 1943) - Živković Milutin D. (Baština, 2018)
Luka Popovic came from one of the most respected families from the area of Pešter, who gave birth to priests and national workers among the local Serbs. He was no exception to this practice, so he chose a church avocation in mature years. He took the parish in village Suvi Do, from his father Milutin, continuing family tradition. During the long-standing work in the interwar period Luka Popovic was dedicated to church affairs, as well as to those of national and cultural significance. This made him a target of the attack by Muslim secessionists from the Tutin region, but also by the Albanian authorities installed in this area after the fall of the Kingdom of Yugoslavia in year 1941. One of these attacks will end Popovic's life two years later. Therefore, his murder must be seen from the context of the long-standing persecution of the Serbs from county of Štavica, as an act that speeded up this process and introduced it to the final stage by the spring of 1944.